ANALISIS ASAS LEX SUPERIOR DEROGAT LEGI INFERIOR DALAM PRESIDENTIAL THRESHOLD DAN REGENT TRESHOLD - Harun Fadhli; Sarip Sarip; Rohadi Rohadi; Nur Rahman (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2021)
The rejection of the judicial review has an impact on Regional Head Elections (Pilkada) throughout Indonesia. Consequently, the Pilkada must follow the same legal provisions as the central provisions regarding the presidential threshold. The difference is only in terms of naming which is called the regent threshold. Researchers, using the regent threshold for studies related to regional elections at the district level, especially the object of which is the Regency. In addition, in the form of regional autonomy, it recognizes the level of legal norms that the law of a lower position may not conflict with the law of a higher position. This means that in a unitary state, the rules that apply at the center will also apply to the regions. Affirmation should be done to avoid confusion or to avoid interpretations between regions, gubernatorial elections, and elections. The threshold for regional heads is inseparable from the existence of the Lex Superior Derogat Legi Inferiori legal principle which regulates how the legal status exists in Indonesia so that the regional head threshold setting is a derivative of the above threshold setting, namely the presidential and vice presidential election threshold. The impact of the Presidential Threshold is not only in the election of regional heads, but also in the election of regents or deputy regents, interim changes for regional heads or deputy regional heads who have a permanent membership. Keywords: Lex Superior Derogat Legi Inferiori, Threshold, Legal provisions.